GENRE BASED APPROACH IN ONLINE LEARNING IN WRITING ANALYTICAL EXPOSITION TEXT - Azhari Yunus (STKIP AL HIKMAH SURABAYA, 2022)
This study shares process genre-based approach and those who are taught by using non-PGBA learning through online learning. First, The application of Genre Based Approach makes students more assisted and helped through implementing the stages of Genre Based Approach. This approach is defined through the number of stages including Building Knowledge of The Field (BKOF), Modeling of the Text (MOT), Join Construction of the Text (JCOT), and Independent of Construction of the Text (ICOT). Second, mind mapping technique was popularized in the late of the 1960s and has been employed in many different areas since the development This technique was introduced as a note taking technique. In short, the mind map and genre-based approach enables the students to write more systematically.